Micro-Fabrication of Organic-Inorganic Hybrid SiO2 Sol-Gel material based on UV-Micropatterning technique - Mat Tamizi Zainuddin (School of Microelectronic Engineering, University Malaysia Perlis, 2014)
Photonics components derived from optical waveguides are key factors in creating a ubiquitous society that support the photonic telecommunications networks. Silica-based planar optical waveguides circuits are promising technologies that provide several photonic devices for practical network due to their transparent properties in optical telecommunication window applications.